2012
DOI: 10.1002/jsfa.5572
|View full text |Cite
|
Sign up to set email alerts
|

Eri silkworm: a source of edible oil with a high content of α‐linolenic acid and of significant nutritional value

Abstract: The study showed that eri silkworm pupae oil is safe and nutritionally equivalent to commonly used vegetable oils. Eri silkworm pupae can be harvested to provide a cost effective alternative edible oil that can be used to nutritional advantage in the food and feed industry. Therefore eri silkworm and its host plants offer an excellent example of multiple product crops and of sustainable agricultural practice with excellent opportunity for economic and nutritional benefits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 30 publications
1
42
0
2
Order By: Relevance
“…This was believed to be thanks to α-linolenic acids which are rich in silkworm pupae [16,22]. That is to say that a high protein diet such as silkworm pupa oil could significantly reduce the TC concentrations in the blood, TG, low-density lipoprotein cholesterol (LDL-C), atherogenic indices, platelet aggregability, etc., compared with the control group, whereas it showed an significantly increased level of high-density lipoprotein cholesterol (HDL-C) [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was believed to be thanks to α-linolenic acids which are rich in silkworm pupae [16,22]. That is to say that a high protein diet such as silkworm pupa oil could significantly reduce the TC concentrations in the blood, TG, low-density lipoprotein cholesterol (LDL-C), atherogenic indices, platelet aggregability, etc., compared with the control group, whereas it showed an significantly increased level of high-density lipoprotein cholesterol (HDL-C) [22].…”
Section: Discussionmentioning
confidence: 99%
“…Palmitoleic acid, oleic acid, and linoleic acid which are fatty acids of dried silkworm pupae account for about 70 percent [15]. As a result of having rats take silkworm pupae oil for 18 weeks, total cholesterol in blood and triglycerides were significantly reduced as well as high-density lipoprotein cholesterol was notably increased [16]. Peptide, which is not a fatty acid of silkworm pupae, is also reported to be effective in inhibiting the synthesis of fat [17].…”
Section: Introductionmentioning
confidence: 99%
“…Eri silkworm feeds on leaves of two major plants, castor and tapioca and it was reported that the pupae fed on tapioca leaves had a higher content of ALA compared to the pupae fed on castor leaves. A recent report suggested that the oil was toxicologically safe and nutritionally equivalent to commonly used vegetable oils with added benefits due to high ALA content (Longvah et al, 2012). In the present study, we report the isolation of ALA from eri silkworm oil and its incorporation into egg PC which could be more economical than the reported methods for the preparation of nutraceutical products with ALA.…”
Section: Introductionmentioning
confidence: 56%
“…The SL prepared contains ALA in similar amounts to soyabean oil and hence, can be tested for the applications where soyabean oil is used to further expand its application. Further studies for producing additional SL with SWO could be of interest based on preliminary evaluation of the SL as SWO is reported to be safe based on its toxicological evaluation (Longvah, 2012). …”
Section: Resultsmentioning
confidence: 99%
“…It was reported that eri silkworm oils contain a high amount of ALA in the range of 45%-55% depending on the feeding source (Kaki, 2006). The oil has been studied for its toxicity and was found that it is equivalent to other vegetable oils and also the oxidative stability of the SWO was shown to be improved when stored with appropriate antioxidants (Thumu, 2015;Longvah, 2012). As part of our research interest on value addition to eri silkworm oil (Ravinder, 2015;Kaki, 2014;Thumu, 2015), we attempted to prepare a SL with eri SWO and PO as substrates.…”
Section: Introductionmentioning
confidence: 99%